2020
DOI: 10.1590/1980-57642020dn14-020004
|View full text |Cite
|
Sign up to set email alerts
|

Action observation combined with gait training to improve gait and cognition in elderly with mild cognitive impairment A randomized controlled trial

Abstract: Abstract. Owing to advancement of medical technology and current knowledge, the population has a longer life expectancy, leading to an increase in the proportion of elderly. Objective: The study aimed to investigate the effect of action observation (AO) combined with gait training on gait and cognition in elderly with mild cognitive impairment (MCI). Methods: Thirty-three participants were randomly allocated to action observation with gait training (AOGT), gait training (GT), and control (CT) groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 32 publications
(46 reference statements)
0
31
0
Order By: Relevance
“…Additionally, four studies implemented interventions longer than 12 weeks (Kounti et al, 2011;Lam et al, 2015;Donnezan et al, 2018;Park et al, 2019). Only three studies had follow-up-up to 1, 3, and 6 months, respectively-and they also reported greater long-term cognitive improvements in combined intervention group (Donnezan et al, 2018;Park et al, 2019;Rojasavastera et al, 2020).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Additionally, four studies implemented interventions longer than 12 weeks (Kounti et al, 2011;Lam et al, 2015;Donnezan et al, 2018;Park et al, 2019). Only three studies had follow-up-up to 1, 3, and 6 months, respectively-and they also reported greater long-term cognitive improvements in combined intervention group (Donnezan et al, 2018;Park et al, 2019;Rojasavastera et al, 2020).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Nine studies of older adults with MCI were eligible (Kounti et al, 2011;Lam et al, 2015;Delbroek et al, 2017;Park, 2017;Donnezan et al, 2018;Mrakic-Sposta et al, 2018;Park et al, 2019Park et al, , 2020Rojasavastera et al, 2020), with 217 participants in the combined intervention group, 41 in the single cognitive intervention group, and 176 in the sham intervention group. Regarding the study design, eight studies were RCTs (Lam et al, 2015;Delbroek et al, 2017;Park, 2017;Donnezan et al, 2018;Mrakic-Sposta et al, 2018;Park et al, 2019Park et al, , 2020Rojasavastera et al, 2020) and one study was NRCT (Kounti et al, 2011).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Nine studies of older adults with MCI were eligible (Kounti et al, 2011;Lam et al, 2015;Delbroek et al, 2017;Park, 2017;Donnezan et al, 2018;Mrakic-Sposta et al, 2018;Park et al, 2019Park et al, , 2020Rojasavastera et al, 2020), with 217 participants in the combined intervention group, 41 in the single cognitive intervention group, and 176 in the sham intervention group. Regarding the study design, eight studies were RCTs (Lam et al, 2015;Delbroek et al, 2017;Park, 2017;Donnezan et al, 2018;Mrakic-Sposta et al, 2018;Park et al, 2019Park et al, , 2020Rojasavastera et al, 2020) and one study was NRCT (Kounti et al, 2011). Regarding the modes of combined intervention, seven studies included simultaneous combined cognitive and physical training (Kounti et al, 2011;Delbroek et al, 2017;Park, 2017;Donnezan et al, 2018;Mrakic-Sposta et al, 2018;Park et al, 2019Park et al, , 2020 and two studies performed sequential combined intervention (Lam et al, 2015;Rojasavastera et al, 2020), all of which reported greater cognitive improvements in the combined intervention.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations